Penggunaan Model Pembelajaran Cooperative Tipe STAD dalam Peningkatan Kemampuan Menelaah Struktur Teks Persuasif Pada Siswa Kelas VIII SMPN 5 Tambun Utara - Suryahadi, Bagus Wijaya; Hartati, Dian; Suntoko, Suntoko (Universitas Lampung, 2024)
The STAD Cooperative Learning model is identified as a crucial factor in enhancing the learning process and outcomes. During observations in the field, researchers encountered a significant challenge: students' limited understanding of persuasive text formats in research tasks. This prompted an investigation into how effective the STAD Cooperative Learning model could be in improving eighth-grade students' comprehension of persuasive text structures at SMPN 5 North Tambun. Using a quantitative approach through quasi-experimental methods, the study employed a Nonequivalent Control Group design. Experimental and control groups were selected from classes VIII 2 and VIII 4, respectively, in a non-random manner from a pool of 181 eighth-grade students, with 33 students sampled from each class. The research proceeded in three stages: Pretest, intervention, and Posttest. Initial assessments (Pretest) gauged students' proficiency in analyzing persuasive texts. Subsequently, the intervention phase involved implementing the modern STAD learning model, supported by carefully designed teaching materials. Following the intervention, Posttests were conducted to evaluate how effective the STAD model was in enhancing students' ability to analyze persuasive text structures. The data analysis included tests for normality, homogeneity, and hypothesis testing. The findings revealed that the Posttest results in the experimental group (averaging 89.50) surpassed those in the control group (averaging 76.22). Moreover, paired t-tests indicated a significant difference (P = 0.000, < 0.05) between Pretest and Posttest scores. Therefore, the STAD Cooperative Learning model proved effective in enhancing eighth-grade students' proficiency in deciphering persuasive text structures. This study underscores the influential role of the cooperative STAD learning model in improving students' grasp of persuasive text structures at SMPN 5 North Tambun.Keywords: STAD type cooperative, persuasive text structures, SMPN 5 North Tambun students